COST-EFFECTIVENESS OF VILANEROL / UMECLIDINIUM VERSUS TIOTROPIUM IN SEVERE AND VERY SEVERE COPD - E. G. Kosolapov; F. S. Kochenkov; N. L. Pogudina; D. V. Blinov (IRBIS LLC, 2017)
In accordance with currently accepted recommendations for the diagnosis and treatment of chronic obstructive pulmonary disease (COPD), both monotherapy with long-acting anticholinergics (LAAC) or combined therapy (LAAC / long-acting beta-agonists, LABA) can be used. To justify a rational choice between these two medications, we used the methodology of clinical/economic analysis.Objective: to assess possible financial and clinical/economic consequences of replacing monotherapy based on LAAC (tiotropium bromide) by the fixed combination of LAAC / LABA (vilantererol / umeclidinum bromide) in patients with severe and extremely severe COPD.Materials and methods. The target population included patients with severe and extremely severe COPD (FEV1 <50%, CAT ≥10, mMRC ≥2, with severe symptoms). QALY (quality-adjusted life-year) was used as the main criterion of effectiveness. Direct medical costs of drug therapy, and the costs of management of adverse events and/or COPD exacerbations were calculated. The costs of these two therapeutic regimens were calculated from the registered data on the maximum selling prices of VED drugs or from the prices expected if/when the given drugs are registered in the VED list (+ VAT + weighted average wholesale premium). Other direct medical costs were calculated in accordance with the Federal program of free medical care, as well as the cost-effectiveness factors recommended by the FFOMS. The obtained values of savings in direct medical costs and the cost-effectiveness ratio (CER) were evaluated for their sensitivity to changes in basic prices of the compared medications.Results. The use of vilantererol / umeclidinum bromide resulted in improved lung function (an increase in FEV1 by 120% on the 169th day, 0.205 vs 0.093), improved quality of life and reduced symptoms, as well as a 63%-lower need for urgent drugs as compared to the tiotropium bromide monotherapy. The quality of life was 0.752 and 0.732 QALY in the group of vilantererol / umeclidinum bromide and tiotropium bromide, respectively. The direct medical costs in these two groups amounted to 32,753 rubles and 37,641 rubles, respectively. Thus, the savings of using the combined medication reached 4,888 rubles, which is 13% less than that with the mono-component drug. If the current practice of treating COPD with tiotropium bromide is replaced by the combined vilantererol / umeclidinum therapy, the total budget savings can reach more than 327 million rubles.Conclusion. The use of vilantererol/umeclidinum for the treatment of severe and extremely severe COPD is strongly preferred over tiotropium bromide, as it leads to significantly better clinical outcomes and provides savings for the health care budget.